Waste management an Islamic perspective - Farida Suldina Achmad (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: The primary goal of the study is to pinpoint the elements that determine the community of Batu Bantar Gebang’s involvement in the creation of a waste bank. Methodology: Methods of qualitative research were applied in this study. Interviews, field observations, and a review of relevant books and periodicals were all used to gather data for the study. The Ummu Amanah Foundation in Sumur Batu District, Al-Falah School, in Bantar Gebang, Bekasi, West Java, served as the study’s location. Findings: The community’s religious beliefs inspire it to recycle rubbish that still has worth. Throughout the entire waste management process, the residents of the village mainly adhered to Quranic teachings. According to Islamic law, every Muslim has a responsibility to preserve the environment, use resources wisely, abstain from various diseases, and commit acts of tabdzir and israf. Additionally, it is prohibited to leave trash where it can still be picked up and used for one’s own and other people’s interests. Implications/Novel Contribution: The general public and upcoming researchers can use the findings of this study as a starting point. Increasing literacy on garbage banks while considering effective teaching techniques and people’s desire to preserve the environment.